(untitled) (Biocenosis, 2021)
On March 11, 2020, the World Health Organization (WHO) declared the Wuhan China respiratory virus outbreak a pandemic. There was no quick mechanism to identify those infected, so it was not possible to apply an isolation procedure that was 100% effective to prevent the spread. This required the application of general rules of physical distancing to the entire population. At the same time, this forced to reduce import, export, production, and consumption employment activities, which of course, caused the fall of markets and economies, leaving millions of people unemployed. Despite this, sanitary measures and free movement restrictions have had a positive impact on the environment, significantly reducing atmospheric emissions. In turn, organizations have implemented many strategies and new ways of working and doing business, which has implied organizational changes and has shown that the best prepared companies are those that make better use of digital technologies. All the above demonstrates the ability of human beings to face crisis, a lesson that can now be applied to a sustainable economic recovery linked to the international climate agenda that seeks to adapt to climate change and, if possible, stop the phenomenon.